2015
DOI: 10.1186/s12951-015-0100-x
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of gold nanocarrier for the delivery of JAG-1 peptide

Abstract: BackgroundUnique properties exhibited by nanoparticles makes them great candidates for applications in physics, chemistry, biology, material science and medicine. The biological applications of water-soluble gold nanoparticles range from contrast agents, delivery vehicles to therapeutics. Notch signaling is a complex network that orchestrates cell fate decisions, which involves proliferation, migration, differentiation and cell death in organisms ranging from insects to humans. Studies have showed that a corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…The CopA3 is a 9-mer peptide (LLCIALRKK-NH 2 ) derived from coprisin [39]. Its amino acid residues were used to covalent coupling to the carboxylic-group-functionalised GNPs [17]. Yang et al [40] suggested that peptidecapped GNPs achieved more cellular internalisation and prolonged intracellular retention compared with citratecapped GNPs because of their positive surface charges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CopA3 is a 9-mer peptide (LLCIALRKK-NH 2 ) derived from coprisin [39]. Its amino acid residues were used to covalent coupling to the carboxylic-group-functionalised GNPs [17]. Yang et al [40] suggested that peptidecapped GNPs achieved more cellular internalisation and prolonged intracellular retention compared with citratecapped GNPs because of their positive surface charges.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations have shown that GNPs are readily bound thiol, amine, and cyanide groups [17]. GNPs have been further functionalised with different complex molecules, including DNA [18], proteins [19], peptides [20], and polymers [21].…”
mentioning
confidence: 99%
“…Another method for JAG1 delivery is functionalizing nanocarriers with JAG1. Matea et al (2015) aimed to develop a route to functionalize gold nanoparticles (GNPs) with JAG1 to promote an efficient interaction between JAG1 and the NOTCH receptor. Two routes were developed and the resulting nanostructures were evaluated in terms of functionality and toxicity.…”
Section: Delivery Methodsmentioning
confidence: 99%
“…Notch ligands are long polypeptides (>500 amino acids) and are thus difficult to modify or immobilize in an orthogonally well-defined fashion through conventional crosslinking methodologies. Shorter ligand-mimicking peptides, such as a 17-amino acid Jag1 DSL domain fragment , have been tested for covalent conjugation to materials [ 52 , 66 , 67 ]. However, these peptides do not appear to be as potent in inducing Notch as the full-length ligands [ 67 ].…”
Section: Activating Notch For Tissue Patterning: Design Consideration...mentioning
confidence: 99%